Talent development: A practitioner guide - Collins, D.; MacNamara, A. (Routledge, 2018)
The process of talent development (TD) is essential to success in any sport. Drawing on the latest evidence and a considerable experience base, this book dispels myths about talent development and offers practical advice on the TD pathway from pre-school to elite level. Aimed at practitioners and other stakeholders involved in the TD process - including coaches, scientists, administrators, educators, students, parents, policy makers and senior development athletes - this is the only up-to-date practical guide to TD in sport.